BRAF inhibitor cessation prior to disease progression in metastatic melanoma: Long-term outcomes. (January 2023) - Lee, Joanna; Ahmed, Tasnia; Maurichi, Andrea; Di Guardo, Lorenzo; Stagno, Anna M.; Warburton, Lydia; Taylor, Amelia. M.; Livingstone, Elisabeth; Rehman, Saba; Khattak, Adnan; Kahler, Katharina C.; Vanella, Vito; et al.
Abstract: Background: BRAF mutant melanoma treated with BRAF ± MEK inhibitor (targeted therapy) has a high response rate; however, most patients progress (PD). Some patients have durable response, but it is unknown whether treatment can be discontinued in these patients. We describe the recurrence risk, progression patterns, response to subsequent treatment, and survival of patients with advanced melanoma who ceased targeted therapy prior to PD. Patients and methods: Ninety-four patients who ceased targeted therapy without progression were identified retrospectively from 11 centres: 45 were male; 81 V600E; 88 stage IV. Fifty-nine were treated with BRAF + MEK inhibitor, and 35 were treated with BRAF inhibitor alone. Median treatment duration was 29.6 months (range 0.36–77.9). At cessation, 67 were in complete response, 21 in partial response, and 2 stable disease. Results: After median follow-up from cessation of 42.9 months (range 0.0–88.7), 36 (38%) progressed; median time to progression was 4.7 months (range 0.7–56.9); 30 (83%) were asymptomatic and 7 (19%) had new brain metastases. Progression rates did not differ by best response: 34% for complete response and 43% for partial response ( P = 0.65). Treatment duration was strongly associated with risk of progression: Median treatment duration was 18.3 (range 0.85–65.7) months for those who progressed and 34.6 (range 0.36–77.9) months for those who did not ( P = 0.0004). Twenty-two received further targeted therapy with 15 (68%) responses. Conclusion: Risk of progression after cessation of targeted therapy is strongly associated with treatment duration. Response to retreatment with targeted therapy is high. Highlights: Thirty eight percent of patients who ceased targeted therapy before PD progressed. There is a strong inverse association between treatment duration and risk of PD. Seventy eight percent of PD events occurred within 12 months of treatment cessation. Best response and depth of response were not predictive of PD risk. Responses to rechallenge with BRAF ± MEK inhibition are common.